Viability of dairy-origin calves for a new beef production enterprise in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Agricultural Science at Massey University, Palmerston North, New Zealand - Hunt, Joshua James (Massey University, 2019)
The New Zealand dairy industry produces approximately 4.2 million calves annually, of which about 30% are retained within the dairy industry, while a further 20% are utilised in the beef industry. The remainder are surplus to requirements, and the majority (1.7 million per annum) are processed in the low value bobby calf trade. This model appears sub-optimal, with an estimated opportunity cost in excess of NZD $1 billion annually, and numerous animal welfare and ethical issues. Farming surplus dairy calves in an accelerated-cycle beef production enterprise for slaughter prior to one-year of age, could generate favourable outcomes, and the current study aimed to investigate this opportunity. Experimental growth and carcass data for Hereford x Friesian-Jersey steers slaughtered at 8-, 10- and 12- months of age was obtained in a live-animal trial. Simulation models (referred to as NGB8, NGB10 and NGB12 where the figures refer to monthly ages at slaughter) utilising Microsoft EXCEL feed budgets, gross margin analysis and the OVERSEER nutrient budget model were developed from the experimental data to estimate the physical, financial, and environmental performance of accelerated-cycle beef production at each slaughter age. Results were compared to a simulated high and low performing bull-beef enterprise based on the literature, with slaughter occurring at 18- or 24-months, to determine the relative performance of accelerated-cycle beef production. The model comparators are referred to as Bull18 and Bull24. In the trial, the accelerated-cycle beef production (NGB) steers achieved slaughter weights of 252, 303 and 348 kg at 8-, 10- and 12-months of age (119, 146 and 174 kg carcass weight). The dressing out percentage was the same in the 8- and 10-month treatments (P>0.05) but increased in the 12-month treatment (P<0.001). Using the ‘prime’ beef price, NGB8 and NGB10 generated a loss, while NGB12 was profitable. To be financially competitive with Bull18 or Bull24, NGB production required a price premium of 11 – 29% above the ‘prime’ beef schedule. There was insufficient evidence to suggest NGB production had a lower nutrient loss footprint, or reduced greenhouse gas output compared to bull-beef production. Further analysis showed weaner genetic merit for growth had a positive relationship with profitability, but no interaction with environmental output under NGB production. Overall, this study demonstrated that Hereford x Friesian-Jersey steers can grow well under typical beef finishing conditions. Given that accelerated-cycle beef production’s environmental output is similar to bull-beef production, profitability is the key determinant of the concept’s viability. Although NGB production with slaughter occurring at 12-months of age was profitable under the ‘prime’ beef classification, a premium of 11 – 29% (depending on slaughter age) would be required for the proposed enterprise to be financially competitive with bull-beef production. However, research has shown the meat derived from this production system is of high quality, therefore there is potential for a price premium if suitable markets are located. Finally, the procurement of weaners with high genetic merit for growth represents an opportunity to further enhance the proposed enterprises overall performance.
Keywords: Calves; New Zealand; Growth; Beef cattle; Carcasses; Beef; Prices; Dual-purpose cattle; Beef industry; 300301 Animal growth and development